2018
DOI: 10.5433/1679-0359.2018v39n4p1683
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive behavior and thermoregulation in sheep fed forage cactus silage undergoing intermittent water supply

Abstract: This study aimed to assess the effect of using forage cactus silage in the diet of sheep under intermittent water supply on its ingestive behavior and thermoregulation. We used in the experiment thirty-six intact male sheep of undefined genotype with an initial average weight of 19.8 ± 2.1 kg and age of approximately six months. The experimental design was a randomized block design in a 3 × 3 factorial scheme composed of three levels of forage cactus silage in the diet (0, 21, and 42%), three water supply peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Thus, the improved intake of spineless cactus in the form of silage when compared with its fresh version is likely not related to the digestibility of the dietary nutrients, but rather to the fermentation products of cactus, which can influence its acceptability by the animals (Nobre et al, 2018;Albuquerque et al, 2020). Nobre et al (2018) evaluated nutrient intake in mixed-breed lambs fed diets with different proportions of spineless-cactus silage and found that the inclusion of 42 % of the ingredient (DM basis) provided DM and NDF intakes of 839.46 and 344.51 g/day, respectively. These results indicate a higher DM intake in comparison with the present experiment, but similar NDF intakes in relation to the CS and CSI diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the improved intake of spineless cactus in the form of silage when compared with its fresh version is likely not related to the digestibility of the dietary nutrients, but rather to the fermentation products of cactus, which can influence its acceptability by the animals (Nobre et al, 2018;Albuquerque et al, 2020). Nobre et al (2018) evaluated nutrient intake in mixed-breed lambs fed diets with different proportions of spineless-cactus silage and found that the inclusion of 42 % of the ingredient (DM basis) provided DM and NDF intakes of 839.46 and 344.51 g/day, respectively. These results indicate a higher DM intake in comparison with the present experiment, but similar NDF intakes in relation to the CS and CSI diets.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cactus-based silages in small ruminant diets is already being studied in different regions of the world such as Tunisia (Abidi et al, 2013), Mexico (Miranda-Romero et al, 2018), Zimbabwe (Gusha et al, 2015a, b), and Brazil (Macêdo et al, 2017(Macêdo et al, , 2018Nobre et al, 2018). These studies reported that cactus-based silages have a good fermentation pattern and can therefore properly preserve the ensiled material.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, vale ressaltar que além de poder ser fornecida in natura ou farelada (Almeida, 2012), outra estratégia pertinente é a de utilizá-la na forma de silagem, sendo esta tecnologia considerada de alto potencial para alimentação animal, especialmente em regiões com escassez hídrica e alimentar (Macêdo et al, 2017;Nobre et al 2018;Brito et al (2020).…”
Section: Palma Forrageira: Cultivo E Uso Em Regiões Semiáridasunclassified
“…It is estimated a planting area that comprises between 500 and 600 thousand hectares of cactus pear cultivation (Dubeux-Junior et al, 2013;Dubeux-Junior, 2016). In this sense, several studies have demonstrated the importance and viability of preserving cactus pear as silage, whether combined with other crops or in the form of a total diet (Nobre et al, 2018;Borges et al, 2019;Pereira et al, 2019;Brito et al, 2020;Matias et al, 2020;Silva-Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%